New Silk Road infrastructure opportunities in developing tourism environment for residents better quality of life - Mamirkulova, Gulnara; Mi, Jianing; Abbas, Jaffar; Mahmood, Shahid; Mubeen, Riaqa; Ziapour, Arash (Global ecology and conservation, 2020)
Residents’ communities feature to make innovative tourism development strategies. Residents play an indispensable role in developing policies and sustainable tourism infrastructure projects. A few research studies have sought to understand the animated influence of sustainable tourism opportunities on residents’ life. The study examines how tourism opportunities enhance residents’ quality of life in the context of the New Silk Road Initiative. The main objective of the current research study is to analyze the interplay of perceived impacts of New Silk Road tourism infrastructure development on local communities’ perception of sustainable tourism development and perceived quality of life. Previous researches were focusing on sustainable tourism projects incorporated various approaches to describe the linkage between the chosen variables. This study built and tested a causal model that specified the direct and indirect interconnections of perceived tourism infrastructure, sustainable tourism development, and residents’ perception of the quality of life. This study incorporated a self-administered questionnaire to collect data sets from Kazakhstan’s residents. The findings indicated that both direct and indirect effects of the New Silk Road Initiative of tourism infrastructure exhibited significant and positive influence on residents’ quality of life through residents’ perceived sustainable tourism development. The results indicated that the New Silk Road Initiative for tourism infrastructure positively effects developing sustainable tourism opportunities, which, in turn, escalates residents’ life quality. Besides, findings are useful in designing the promotions of sustainable tourism governance and residents’ welfare under New Silk Road Infrastructural Projects. However, solely tourism infrastructure strategies cannot improve residents’ quality of life. Economic, social, cultural, and environmental factors are vital to developing sustainable tourism at the destinations and need concentration to stimulate and ensure the positive impact of tourism infrastructure on specific beneficial outcomes. The findings’ implications are useful in developing more infrastructure projects in Kazakhstan.